Protecting the organization against risk and the role of financial audit - Sylwia Bozek; Izabela Emerling (Institute of Economic Research (IER), 2015)
In the contemporary economic reality and organization's activities aiming at effectiveness and efficiency of functioning, a lot of significance is attached to a financial audit as an important instrument for protecting the organization against the risk factors. The aim of this article is to present theoretical and practical (on the basis of the examined example) aspects concerning the (internal) financial audit in the organization within the context of its assessment of the exposure to risk. The applied research methods are based on the method of conceptual analysis of the literature on the examined field, as well as on the case study of the auditing task. The results of the performed analyses and examinations allow to state that the financial audit constitutes an effective tool for protecting the organization against internal, as well as external risks. Each of the co-authors will contribute 50% of work to this article.
Keywords: D81; M42; 330; risk; risk identification; risk management; financial audit; internal audit